Sebaran Kinerja Daerah Irigasi Pasca Penyerahan Pengelolaan Irigasi - Murtiningrum Murtiningrum; Wisnu Wardana; Ni Nyoman Sulastri (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
One among the policies in Irrigation Management Policy Reform (IMPR) is the Irrigation Management Transfer (IMT). Through the IMT, farmers in Water Users' Association (WUA) manage their own irrigation systems. The IMT let farmers to diversify their farming system to achieve farmers' welfare. The diversification results in in the variation of planting pattern in an irrigation system. The variation is bigger if market plays a role in crop choice. Therefore, the assumption that an irrigation system has a uniform performance throughout the system is no longer valid. This paper aims to examine the distribution of an irrigation system managed by farmers. The system chosen as sample was Mejing Irrigation System in Banjul, Yogyakarta. The performance was assessed by using adequacy and water delivery performance. The spatial distribution of Mejing Irrigation System is mainly affected by irrigation operation pattern as well as condition and serviceability of irrigation network Spatially, the tertiary blocks located in the head receive more water than other tertiary. blocks in the tail.